Implementation of Troubleshooting Teaching Method to Develop Student's Competency in Conducting Motorcycle Tune-up. (November 2019) - Arsana, I M; Susila, I W; Hidayatullah, R S; Ariyanto, S R
Abstract: Lack of media used in teaching and the conventional method used are also become the factors which influence the less student's competency achieved in practical learning of motorcycle tune-up. This study aims to develop the student's competency in motorcycle tune-up by applying the Troubleshooting teaching method towards undergraduate students in Education of Mechanical Engineering department. This study used Classrom Action Research (CAR) which used 26 students as subject. They are Undergraduate Student in department of Education of Automotive Mechanical Engineering, Unesa, Indonesia. This study used test method to evaluate the student's competency in motorcycle engine tune-up. Based on the achieved data, it is then analyzed descriptively. This troubleshooting teaching method was able to develop student's study result (student's competency), started from 81, 6 in cycle 1, then 83, 3 in cycle 2, and 87, 1 in cycle III. The completeness of classical study started from 53, 8% in cycle 1, grew to 57, 5% in cycle II, then reached 88, 5% in the last cycle.